PROSES COLLABORATIVE GOVERNANCE DALAM PENANGANAN LINGKUNGAN KUMUH PERKOTAAN (STUDI PADA PELAKSANAAN PENATAAN LINGKUNGAN PERMUKIMAN BERBASIS KOMUNITAS (PLPBK) DI PROGRAM KOTA TANPA KUMUH KABUPATEN PONOROGO) - Hastuti, Dian Meriyana (JI@P, 2020)
The Implementation of Community-Based Settlement Environment Structuring ofthe City without Slums Program in Ponorogo Regency also cannot be separatedfrom good collaboration between the community, the government, the privatesector and other stakeholders. This slum handling cannot be handled if only doneby one or two parties, but requires the participation of various parties orstakeholders who collaborate collaboratively. This study aims to determine theprocess of Collaborative Governance in the Implementation of Community-BasedSettlement Environmental Structuring in the Slumless City Program in PonorogoRegency. The theory used includes the theory of good governance, the process ofcollaboration, environmental development and the concentration of City WithoutSlums. Data collection techniques were carried out by interviewing and observingthe informants using the purporsive sampling method. The data analysistechnique is done by descriptive method. The conclusion of this research is thatthe collaborative governance process has been carried out well starting from thedynamics of Collaboration, Collaborative Actions, and the Temporary Impactsand Temporary Adaptations of the Collaboration Process. Most of it is done in theform of participation at all stages of development.